(untitled) (Northern International Medical College Journal, 2023)
Diagnosis of SARS-CoV-2 infection is based on detection of viral RNA by RT-PCR of nasopharyngeal or oropharyngeal swabs. Consider alternative diagnoses in children who are unwell, even in the presence of a positive SARS-CoV-2 PCR result. Children with mild to moderate Covid19 do not routinely need admission or investigations such as blood tests and radiology, unless otherwise clinically indicated. Children with severe or critical disease as a minimum should have the following investigations: Blood cultures, Full Blood Count (FBC), Coagulation profile, D-dimer, Urea and Electrolytes, LFT, CRP, Troponin, Ferritin, Lactate dehydrogenase (LDH) and Blood Gas Analysis. Remdesivir may be considered for children > 12 years and >40kg with COVID-19 requiring supplemental oxygen. Consider chest x-ray in children who do not follow the expected clinical course, for example, those still requiring oxygen on day three of admission, those with worsening hypoxemia or those requiring respiratory support. Decision to escalate respiratory support to Non-Invasive Ventilation (NIV) should be made by a senior member of the pediatric team, in discussion with critical care. For children with clinical findings consistent with the Pediatric Inflammatory Multisystem Syndrome temporally associated with SARS-CoV-2 (PIMS-TS) should be managed as per specialized guidelines. Northern International Medical College Journal Vol. 12 No.2 Jan 2021, Page 548-554